2021
DOI: 10.1088/1402-4896/ac29db
|View full text |Cite
|
Sign up to set email alerts
|

Tritium in plasma-facing components of JET with the ITER-Like-Wall

Abstract: The ITER-Like-Wall project has been carried out at the Joint European Torus (JET) to test plasma facing materials relevant to ITER. Materials being tested include both bulk metals (Be and W) and coatings. Tritium accumulation mechanisms and release properties depend both on the wall components, their location in the vacuum vessel, conditions of exposure to plasma and to the material itself. In this study, bulk beryllium limiter tiles, plasma-facing beryllium coated Inconel components from the main chamber, bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Pajuste et al examined T retention in Be tile PFSs by the dissolution method [11]. The T retention reported was smaller by a factor of 2-10 depending on the specimen location than the values evaluated in our previous papers [12,13] and those given in figure 10.…”
Section: Two-dimensional Tritium Distributionmentioning
confidence: 67%
See 2 more Smart Citations
“…Pajuste et al examined T retention in Be tile PFSs by the dissolution method [11]. The T retention reported was smaller by a factor of 2-10 depending on the specimen location than the values evaluated in our previous papers [12,13] and those given in figure 10.…”
Section: Two-dimensional Tritium Distributionmentioning
confidence: 67%
“…This difference can be ascribed, at least in part, to non-uniformity of T distributions in the tokamak and to differences in the measurement techniques. Nevertheless, it was reported in [11] that the highest T retention among the specimens examined was measured in the erosion zone (central part) of the OPL. This gives a strong indication that the results obtained by means of the IP technique and dissolution method show a similar tendency.…”
Section: Two-dimensional Tritium Distributionmentioning
confidence: 83%
See 1 more Smart Citation
“…This could be expected, since at present only trace amounts of T are present in JET-ILW tiles. This is due to the fact that between the installation of ILW and extraction of the tiles used for the measurements following the ILW3 campaign, only H and D were used in JET, and thus all the T present comes either from implantation of energetic T produced in the D-D reaction or neutron-induced transmutation of Be, in addition to residual inventory from the previous D-T campaign in 1997 (pre-ILW) [92]. On the other hand, T contents obtained in dissolution measurements do not result from QMS-based detection of molecular species but derive from the direct measurements of radioactivity of released T. This activity can be accurately measured even at very low T concentrations, and these measurements are not affected by the molecular state of T. Therefore, it can be concluded that at the current T levels in Be tiles of JET-ILWnamely, on the order of 10 12 atoms cm −2 -measurements of QMS-based TDS do not allow reliable quantification of T content and distribution.…”
Section: Measurements Of Tritium Retentionmentioning
confidence: 99%